Management of Aries and Aruana Guinea grass cultivars under rotational stocking based on canopy light interception. (30th July 2021) - Campos, F. P.; Sarmento, P.; Mattos, W. T.; Gerdes, L.; Carnevalli, R. A.; Lima, C. G.
Abstract: Efforts were made to obtain forage cultivars with high production capacity and quality and to determine the ideal time to start animal grazing, respecting the morphological characteristics of the grasses. For this purpose, the nutritional value, digestibility and characteristics of the forage canopy of Aries and Aruana ( Megathyrsus maximus (Jacq.) or Panicum maximum ) cultivars kept under rotational stocking with sheep were evaluated and the management height was determined based on 95% light interception (LI). The experiment was evaluated with repeated measures over time (grazing cycles by season, in 2 years) with a treatment factor (grass cultivar) in a completely randomized block design with eight replicates, using 800 m 2 paddocks. The height of the forage canopy before grazing (pre-grazing) determined by 95% LI stabilized around 29 cm. The highest proportion of Aruana leaf blades was observed in winter. Aries grass presented similar leaf blade percentages in summer, autumn and spring. Similar forage accumulation (FA) was observed for both cultivars, decreasing in spring, autumn and winter. Higher crude protein and in vitro dry matter digestibility ( IV DMD) were seen in Aries grass, while Aruana grass presented higher neutral and acid detergent fibre and cellulose and lower IV DMD. The nutritional quality of the grasses was maintained throughout the year. The height of the forage canopy of Aries and Aruana recommended for entry into the paddock is 29 cm to maintain nutritional quality. The successful management strategy adopted for grasses combined with nitrogen fertilization provided a greater forage mass quality.